The gestational age‐specific difference in birthweight between singletons born after fresh and frozen embryo transfer: A cohort study. (11th January 2023) - Ding, Qiaoqiao; Wang, Yuhuan; Suo, Lu; Niu, Yue; Zhao, Dingying; Yu, Yunhai; Wei, Daimin
Abstract: Introduction: Accumulating studies have suggested singletons born after frozen embryo transfer (FET) were higher than those born after fresh embryo transfer (Fre‐ET). However, fewer studies had investigated the gestational age‐specific between‐group difference in birthweight. This study aimed to investigate the gestational week‐specific difference in singleton birthweight after FET vs Fre‐ET and explore potential factors that impact the difference. Material and methods: In this retrospective cohort study, a total of 25 863 singletons were included. Multivariable linear regression and logistic regression were used to evaluate the between‐group differences in mean birthweight and the incidences of large for gestational age (LGA) and small for gestational age (SGA), respectively. Results: Multivariable regression analyses showed a statistically significant interaction between types of embryo transfer (ie FET vs Fre‐ET) and the gestational week on mean birthweight ( P < 0.001) and on the risks of large for gestational age ( P = 0.001) and small for gestational age ( P < 0.001). When stratified by gestational week, the differences in mean birthweight and the risks of LGA and SGA were only observed in singletons born at 37 gestational weeks or later. After adjusting for confounders, full‐term but not preterm singletons born after FET had a higher birthweight (3497.58 ± 439.73 g vs 3445.67 ± 450.24 g; adjusted mean difference 58.35 g; 95% confidence interval [CI] 38.72–77.98 g), a higher risk of LGA (24.3% vs 21.1%; adjusted odds ratio [OR] 1.28, 95% CI 1.15–1.42) and a lower risk of SGA (3.1% vs 4.8%; adjusted OR 0.61, 95% CI 0.53–0.70) compared with those born after Fre‐ET. Conclusions: The differences in birthweight between FET and Fre‐ET were observed in full‐term singletons but not preterm singletons. Abstract : Statistically significant differences in birthweight between frozen embryo transfer and fresh embryo transfer were found at 37 gestational weeks at birth or later. The between‐group differences seemed to occur earlier in women with a higher estradiol level on the day of hCG trigger.